Answer:
[tex]y=\frac{-3}{4} x+3[/tex] in standard form is 3x + 4y = 12
Solution:
Given that [tex]y=\frac{-3}{4} x+3[/tex]
To write a linear equation in standard form, follow the below steps:
The general form of equation is Ax + By = C
[tex]y=\frac{-3}{4} x+3[/tex]
On cross-multiplication we get,
[tex]y = \frac{-3x + 12}{4}[/tex]
Move 4 from denominator of right side to left side
[tex]4y = -3x + 12[/tex]
On rearranging the terms we get
3x - 12 + 4y = 0
3x + 4y = 12
Thus the [tex]y=\frac{-3}{4} x+3[/tex] in standard form is 3x + 4y = 12